(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is devoted to pedagogical issues of providing environmental education to students. Also, the content of the article details such issues as the role of environmental education in human life, the formation of environmental consciousness in students, the interaction of the environment and man, biological, pedagogical conditions for preserving ecomuhit, biological, environmental criteria for nature protection, didactic tools that form environmental consciousness in the individual, specific aspects of environmental education, the formation of a healthy lifestyle.